Synthesis and Characteristics of Cu(II)-Imprinted Silica Gel Sorbent - Ding, Lan-Lan; Long, Su-Qun; Zhou, Yin-Hang; Deng, Yi (Asian Journal of Chemistry, 2012)
In this study, a new Cu(II)-imprinted silica gel sorbent was synthesized by a surface imprinting technique for selective extraction or preconcentration of Cu(II). Compared with non-imprinted polymer particles, the Cu(II) ion-imprinted silica gel had higher selectivity and for Cu(II). The maximum static adsorption capacity of the Cu(II)-ion-imprinted silica gel for Cu(II) was 25.679 mg/g. Results suggested that Cu(II)-ion-imprinted polymers was a material of efficient, low-cost for Cu(II) separation and concentration.